Perancangan dan Implementasi Perangkat Akuisisi Data dan Regulasi Daya pada Sistem - Christopher; Ramadhan, M Rizki; Ramadhani, Inda Dwi; Sahlendar, Rheyuniarto; Istiqphara, Swadexi (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2021)
Health is a very important need for humans, health can be obtained by doing sports. the development of technology makes Virtual Reality can be used as a medium to do sports from home. Through this research has been designed and implemented data acquisition and power regulation devices on virtual reality controller systems for sports. the system will be mounted on the bike as a controller. Waterfall research method consists of several stages, namely review, design, verification of components, implementation and testing. Sensor readings will be sent via a series of bluetooth communications in a data packet. The test results can be concluded that the infrared sensor reading has an error of 0.011%, a potentiometer of 0.047%, and a voltage sensor of 0.002% and has a system average current value of 0.93A.